Lavender Marriage: Between a Solution and the Normalization of Sexual Deviance in the Perspective of Fiqh Principles - Endah Mustika Pertiwi (Lembaga Yasin AlSys, 2026)
Lavender marriage, understood as a heterosexual marriage in which one or both spouses conceal a non-heteronormative sexual orientation, has emerged as a response to social stigma, familial expectations, and cultural pressure. Although such marriages may function as pragmatic strategies for obtaining social acceptance, their compatibility with the ethical and substantive objectives of Islamic marriage remains contested. This study aims to assess the normative validity of lavender marriage within Islamic family law through the jurisprudential maxims al-umūr bi maqāṣidihā (matters are judged according to their intentions) and darʾ al-mafāsid muqaddam ʿalā jalb al-maṣāliḥ (preventing harm takes precedence over attaining benefit). The study employed a normative legal method with a descriptive-analytical approach, drawing on legal sources, classical Islamic jurisprudential literature, and contemporary scholarly publications. The findings indicate that although lavender marriage may satisfy the formal legal and administrative requirements of marriage, it does not fulfill the substantive objectives of Islamic marriage (maqāṣid al-nikāḥ), which emphasize sincerity, mutual affection, tranquility, and honesty between spouses. The application of the two jurisprudential maxims further demonstrates that the potential psychological, familial, and social harms associated with lavender marriage outweigh its perceived benefits as a means of achieving social acceptance. The study concludes that the validity of marriage within Islamic family law should not be assessed solely through formal legal requirements but should also account for marital intentions, ethical objectives, and broader consequences for the parties involved. These findings contribute to contemporary Islamic family law by offering a jurisprudential framework for evaluating emerging marital practices in accordance with the substantive purposes and harm-prevention principles of the Sharīʿah.